Model Persamaan Kumulatif Muatan dan Tinggi Draft Tongkang Terhadap Kumulatif Cycle Time Batu Bara di Pelabuhan Karya Citra Nusantara Marunda - Geby Thesya Paskarina; Hartati M Pakpahan (Jurnal Serambi Engineering, 2023)
AbstractKarya Citra Nusantara Marunda Port is one of the ports that is a port business entity in Indonesia; this port can carry out bulk products unloading activities, including coal, sand, and others. The quantity of cargo in the barge increases as the draft of the barge falls, and vice versa; when the draft of the barge begins to rise, the amount of cargo drops gradually and the excavator's unloading time increases. Considering this, research must be done to ascertain the mathematical model relating to the duration of coal unloading at Marunda Port and to establish the cumulative impact of cargo volume and barge draft height. A multiple linear regression equation model was created for the time of coal unloading using the enter method, Y = -152.076 + 16.157X1 - 148.304X2, based on the findings of the analysis of traditional assumptions and hypotheses that was conducted as a prerequisite for creating a good equation model. The unloading cycle time will be 152,076 minutes shorter with the unloading time per barge when the amount of cargo per tonne drops. The needed unloading cycle time will be increased if the cargo volume rises by 16,157 tons.Keywords: port, unloading time, cycle time, total load, draft height, multiple linear regression